Greater numbers of nucleotide substitutions are introduced into the genomic RNA of bovine viral diarrhea virus during acute infections of pregnant cattle than of non-pregnant cattle - Neill, John D (BioMed Central, 2012)
BACKGROUND: Bovine viral diarrhea virus (BVDV) strains circulating in livestock herds show significant sequence variation. Conventional wisdom states that most sequence variation arises during acute infections in response to immune or other environmental pressures. A recent study showed that more nucleotide changes were introduced into the BVDV genomic RNA during the establishment of a single fetal persistent infection than following a series of acute infections of naïve cattle. However, it was not known if nucleotide changes were introduce when the virus crossed the placenta and infected the fetus or during the acute infection of the dam. METHODS: The sequence of the open reading frame (ORF) from viruses isolated from four acutely infected pregnant heifers following exposure to persistently infected (PI) calves was compared to the sequences of the virus from the progenitor PI calf and the virus from the resulting progeny PI calf to determine when genetic change was introduced. This was compared to genetic change found in viruses isolated from a pregnant PI cow and its PI calf, and in three viruses isolated from acutely infected, non-pregnant cattle exposed to PI calves. RESULTS: Most genetic changes previously identified between the progenitor and progeny PI viruses were in place in the acute phase viruses isolated from the dams six days post-exposure to the progenitor PI calf. Additionally, each progeny PI virus had two to three unique nucleotide substitutions that were introduced in crossing the placenta and infection of the fetus. The nucleotide sequence of two acute phase viruses isolated from steers exposed to PI calves revealed that six and seven nucleotide changes were introduced during the acute infection. The sequence of the BVDV-2 virus isolated from an acute infection of a PI calf (BVDV-1a) co-housed with a BVDV-2 PI calf had ten nucleotides that were different from the progenitor PI virus. Finally, twenty nucleotide changes were identified in the PI virus of a calf born to a PI dam. CONCLUSIONS: These results demonstrate that nucleotide changes are introduced into the BVDV infecting pregnant cattle at rates of 2.3 to 8 fold higher then during the acute infection of non-pregnant animals.